2021
DOI: 10.1007/s11255-021-02794-x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) and impaired kidney function: a 3-year observational study

Abstract: Background Myocardial infarction with nonobstructive coronary arteries (MINOCA) constitutes about 10% of the cases of acute coronary syndromes (ACS). It is a working diagnosis and requires further diagnostics to determine the cause of ACS. Methods In this study, 178 patients were initially diagnosed with MINOCA over a period of 3 years at the Department of Invasive Cardiology of the University Clinical Hospital in Białystok. The value of estimated glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Hyperuricemia also independently predicted the risk of mortality and MACE in patients who underwent cardiac revascularization and cardiac valve surgery (37). Two recent MINOCA studies reported that renal impairment was associated with mortality in MINOCA patients (38,39), the latter study also found that every third patient with MINOCA is diagnosed with impaired kidney function, which implies that the uric acid may play a significant role related to the extent of impaired cardiovascular and/or renal hemodynamics in patients with MINOCA. To our knowledge, no prior study has evaluated the association between hyperuricemia and MINOCA and its impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia also independently predicted the risk of mortality and MACE in patients who underwent cardiac revascularization and cardiac valve surgery (37). Two recent MINOCA studies reported that renal impairment was associated with mortality in MINOCA patients (38,39), the latter study also found that every third patient with MINOCA is diagnosed with impaired kidney function, which implies that the uric acid may play a significant role related to the extent of impaired cardiovascular and/or renal hemodynamics in patients with MINOCA. To our knowledge, no prior study has evaluated the association between hyperuricemia and MINOCA and its impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, they differentiated two subgroups with eGFR < 60 and ≥ 60 mL/min/1.73 m 2 . At 12 months, the all-cause death was 26.42% vs. 7.20% ( p = 0.0004), and after 36 months, it was 33.96% vs. 9.6% ( p < 0.0001) [ 26 ]. In our study, only 3.6% of patients had chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors are presented in Table 1. COPD [9] Obstructive sleep apnea [10] Past stroke [11] Peripheral artery disease [12] Chronic kidney disease [13,14] Anemia [15] Hyperuricemia [16][17][18] Hyperfibrinogenemia [19] Thyroid hormone dysfunction [20] Rheumatoid arthritis [21] Psychiatric disorders [22] * Sexual disorders [23] * Socioeconomic factors [24] * Pregnancy and reproduction-related disease [25,26] *…”
Section: Introductionmentioning
confidence: 99%